Exploring the Relationship Between Smartphone Addiction and Sleep Quality in Adolescents - Farisa Nadhira Zahra; Mahargyantari Purwani Dewi (Jurnal Kesehatan dan Kedokteran, 2026)
Adolescence is a critical period of development marked by significant physical, cognitive, and emotional changes. However, with the rise of smartphone use, adolescents face challenges related to their sleep quality. Excessive smartphone use, especially at night, has been linked to disrupted sleep patterns, which can negatively affect their health and well-being. Objective: This study aims to explore the relationship between smartphone addiction and sleep quality in adolescents. The primary goal is to understand how smartphone addiction influences sleep duration, sleep disturbances, and overall sleep quality, which is crucial for the health and functioning of adolescents. Methodology: A quantitative approach was used in this research, employing two standardized scales: one for measuring sleep quality and another for assessing smartphone addiction. Data were collected from adolescents aged 12 to 20 years who met the inclusion criteria of owning a smartphone, using it for at least five hours daily, and engaging in nighttime smartphone use. Simple regression analysis was used to examine the correlation between smartphone addiction and sleep quality. Findings: The results revealed a significant negative correlation between smartphone addiction and sleep quality. Adolescents with higher levels of smartphone addiction exhibited poorer sleep quality, characterized by shorter sleep duration, more frequent awakenings, and reduced feelings of refreshment upon waking. These findings highlight the detrimental impact of excessive smartphone use on adolescent sleep. Implications: This research contributes to the understanding of how smartphone addiction affects sleep quality among adolescents. The findings suggest that managing smartphone use could be a vital factor in improving sleep quality, which in turn may enhance overall adolescent health and well-being. This study offers a foundation for future interventions aimed at promoting healthier smartphone usage patterns among adolescents. Originality: This study provides new insights into the specific impact of smartphone addiction on sleep quality in adolescents, particularly in the Indonesian context. The research offers a unique perspective compared to previous studies and adds valuable data to the broader field of digital health and adolescent well-being.